(untitled) (Oratio Directa, 2022)
This study examines the communication role of Duta Harmoni, also referred to in the program as Duta Damai Dunia Maya, in countering online radicalism propaganda. It focuses on three issues: the ambassadors' communication activities, their coordination with the Pusat Media Damai, and the barriers encountered in implementing the program. The study uses a qualitative case-study approach. Primary data were obtained through non-participant observation and interviews, while secondary data were drawn from relevant literature. The findings show that online activities include building virtual networks, monitoring potentially harmful content, reporting findings, producing and distributing peace-oriented content, and managing websites. Offline activities include workshops, classes, socialization, and focus-group discussions for young people. Coordination with the Pusat Media Damai takes place through two-way functional communication concerning monitoring, content themes, and work programs. The main barriers are unequal internet access, competing work and study obligations, status and generational differences, geographical distance, and differences in educational background and frames of reference. The results support continuous evaluation, more focused recruitment, and practical training in digital communication, religious literacy, argumentation, and search-engine optimization. Because the source does not report participant numbers or validation procedures, the findings are interpreted as a bounded case description rather than a general measure of program effectiveness.